UR_GERICHTE 2018_OG V 17 47. vom 12. Januar 2018 - UR Obergericht (2018)
Kindesschutz. Art. 307 Abs. 1, Art. 310 Abs. 1, Art. 314 Abs. 1 i.V.m. Art. 445 Abs. 1 ZGB. Entscheid über vorsorgliche Massnahmen.